(3efgGL GdWGdHjf hYeOI GdeaJjfs - (3GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjGA, eMj GdOjf, jMj Hf TQa Hf eQj, J (B676(3g`s
(3ChdgG (B:s
( (3cJGH GdaQGFV (B) : (3jHOC ef JQcI GdejJ HeDfI JLgjRg Ke fbV Ojhfg Ke hUGjGg ef KdK GdHGbj Ke jbSe GdHGbj Hjf GdhQKIs
(3BNQgG (B:s
( (3cJGH CegGJ GdChdGO (B) : (3hdh hdOJ ef RhL Ch RfG aGdhdO ddSjO jYJb HehJg cgj hChdGOgG bHd GdGSJjdGO ef RhL Ch RfG dG jYJbhf HehJ GdSjO hdg HjYge hYJb ef QCS GdeGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 149s
(3eYLe GdeDdajf (B4 / 98s
(3cTa GdXfhf (B2 / 1873s
(3TPQGJ GdPgH (B5 / 354s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs